2013
DOI: 10.1111/adb.12043
|View full text |Cite
|
Sign up to set email alerts
|

Relapse to cocaine-seeking after abstinence is regulated by cAMP-dependent protein kinase A in the prefrontal cortex

Abstract: Abstinence from cocaine self-administration (SA) is associated with neuroadaptations in the prefrontal cortex (PFC) and nucleus accumbens (NAc) that are implicated in cocaine-induced neuronal plasticity and relapse to drug-seeking. Alterations in cAMP-dependent protein kinase A (PKA) signaling are prominent in medium spiny neurons in the NAc after repeated cocaine exposure but it is unknown whether similar changes occur in the PFC. Because cocaine SA induces disturbances in glutamatergic transmission in the PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 51 publications
0
22
0
2
Order By: Relevance
“…Postsynaptic mechanisms may also contribute. On WD7, PKA phosphorylation of GluA1 and CREB was increased in the dorsal mPFC and intra-mPFC infusion of a PKA inhibitor reversed this effect and decreased cue-induced cocaine seeking 76 . These latter results suggest that strengthened AMPAR transmission in the mPFC may contribute to incubated cocaine seeking, given that PKA phosphorylation of GluA1 primes AMPAR for synaptic insertion in PFC neurons 77 .…”
Section: Medial Prefrontal Cortexmentioning
confidence: 96%
“…Postsynaptic mechanisms may also contribute. On WD7, PKA phosphorylation of GluA1 and CREB was increased in the dorsal mPFC and intra-mPFC infusion of a PKA inhibitor reversed this effect and decreased cue-induced cocaine seeking 76 . These latter results suggest that strengthened AMPAR transmission in the mPFC may contribute to incubated cocaine seeking, given that PKA phosphorylation of GluA1 primes AMPAR for synaptic insertion in PFC neurons 77 .…”
Section: Medial Prefrontal Cortexmentioning
confidence: 96%
“…For example, our recent studies demonstrated that normalizing the prefrontal ERK signaling pathway during the early withdrawal from repeated cocaine exposure leads to a long-term inhibitory effect on cocaine relapse 120,121 and restores the extracellular glutamate dysregulation in the NAc 260 . In contrast, after prolonged withdrawal from cocaine, an increase of PKA-mediated signaling is dominant in the PFC and NAc responsible for cocaine seeking 85,121,261263 , implicating that ERK activity in the PFC-NAc projection is dynamically regulated by multiple intracellular pathways. Future studies will evaluate the ability of novel therapeutic interventions to restore normal ERK signaling activity in the brain for inhibiting addictive drug-seeking behavior.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“…However, intervention immediately after cocaine self-administration ends is critical because phospho-ERK levels in the prelimbic cortex do not differ from yoked-saline control values one day or one week after the end of cocaine self-administration (Whitfield et al, J Neurosci 2011-supplementary figure 1). Moreover, phospho-CREB levels are normal at 24 hr and elevated one week later and the latter increase is mediated by PKA, not ERK (Sun et al, Addiction Biol 2014). Further, because the suppressive effect of BDNF on cocaine-seeking is ERK-dependent (Whitfield et al, 2011), if BDNF is infused one week after the end of cocaine self-administration when ERK levels in PFC are normal, BDNF has no effect on reinstatement (Berglind et al, 2007).…”
Section: Introductionmentioning
confidence: 99%